The study of the sungura musicians at Diamond Studios: challenges and proposals. - Matarutse, Mabasa Clide (Midlands Sate University, 2015)
The research’s main objective was to study how sungura musicians at Diamond Studios engage in music business, tracing the challenges that hinder the development of music business and find in possible ways to alleviate these challenges for the benefit of sungura musicians at Diamond Studios and the music industry respectively. To gather data, I used questionnaires, observation guide and interviews as research tools and also a purposive sampling to select the respondents. It was noted in this research that, Diamond Studios has played a pivotal role in assisting many sungura musicians with positive business contracts. I have managed to highlight that, financial instability, piracy, and inadequate recourses to run music business are some of the challenges that are being faced by sungura musicians. On the other hand, there is need for a firm business partnership between sungura musicians and the record label. The sungura musicians are encouraged to comply with what Diamond Studios is advocating as for the music business to grow. Also strategies like effective marketing and mass productions are mentioned in this research as a way to curb piracy. This research recommends the government to establish policies that are favourable to musicians and promote music business.